POTENTIAL OF SMART FABRICS IN PASSIVE STIMULATION OF MUSCLE MEMORY - Sarnov, Igor (SWorldJournal, 2025)
The article focuses on analyzing the potential of intelligent textile materials in the context of their ability to passively stimulate muscle memory, with applications in medical, rehabilitation, and everyday settings. The aim of the study is to systemati